Learning from Experience Volume I: Lessons from the Submarine Programs of the United States, United Kingdom, and Australia - Schank, John F. (RAND Corporation, 2011)
The United States, the United Kingdom, and Australia asked the RAND Corporation to develop a set of lessons learned from previous submarine programs that could help inform future program managers. This volume presents an overview of five submarine programs in the three countries-the UK's Astute program; the U.S. Navy's Ohio, Seawolf, and Virginia programs; and Australia's Collins program-and identifies lessons that apply to all of them.